Psychoeducation Stop Bullying For Better Future Among Students Of SMK 2 Penajam Paser Utara - Sukeksi Dyah Intanningrum; Hesti Perwatih; Iswinarti Iswinarti (Green Publisher Indonesia, 2024)
The objective of the psychoeducational program